2018
DOI: 10.1177/2042018818758621
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of diabetic retinopathy among people with diabetes in Jeddah, Saudi Arabia

Abstract: Despite having good awareness about DM and its effects on eyes, the patients exhibited a relative lack of awareness about DR. Considering the association of DR with DM, its increasing magnitude is a potential burden on the community and health systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
44
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 42 publications
6
44
1
Order By: Relevance
“…Funatsu et al (23) reported that while more than 98% of patients were aware of diabetic eye disease, only 69.5% of the patients visited the ophthalmologist for periodic eye examinations. The same nding has been described by alzahrani et al (24) which revealed that 82.6% of his sample were aware of DM complications in their eyes, however, only 65% had their eye checkups regularly. This could be due to many reasons other than lack of knowledge, such as, lack of time, transportation di culties, and lack of family support.…”
Section: Discussionsupporting
confidence: 83%
“…Funatsu et al (23) reported that while more than 98% of patients were aware of diabetic eye disease, only 69.5% of the patients visited the ophthalmologist for periodic eye examinations. The same nding has been described by alzahrani et al (24) which revealed that 82.6% of his sample were aware of DM complications in their eyes, however, only 65% had their eye checkups regularly. This could be due to many reasons other than lack of knowledge, such as, lack of time, transportation di culties, and lack of family support.…”
Section: Discussionsupporting
confidence: 83%
“…Diabetes mellitus (DM) is a chronic debilitating disease that constitutes a substantial problem in both developing and developed nations. This disease is one of the major challenges facing health-care systems due to the remarkable financial burden associated with its multiple comorbidities and high mortality rates [1]. The epidemic of diabetes is a worldwide problem, but its increasing burden is higher in developing countries [2].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of these numerical increments will occur in developing countries [2]. In Saudi Arabia, about one-fourth of people live with diabetes [1].…”
Section: Introductionmentioning
confidence: 99%
“…Type 2 diabetes mellitus (T2DM) is characterized by increased blood glucose due to insulin deficiency caused by pancreatic β‐cell dysfunction and insulin resistance in target organs , affecting more than 370 million people worldwide . Hyperglycemia could lead to critical complications including kidney disease , cardiovascular disease , diabetic retinopathy , etc. Insulin sensitizers such as metformin are prescribed worldwide for lowering blood glucose level and increasing insulin sensitivity.…”
Section: Introductionmentioning
confidence: 99%